Narrative access to Un mundo para Julius - Rodríguez-Peralta, Phyllis W (Pontificia Universidad Católica del Perú. Fondo Editorial, 2004)
Un mundo para Julius (1970),1 first novel of Alfredo Bryce Echenique, belongs among the contemporary literary works which are structured from the temporal and spatial con tours of Lima. But Bryce' s literary space consists of the limeño world of the very wealthy (la oligarquía criolla), and all other segments of the social order are seen in their relationships with the privileged class. Thus Bryce extends the boundaries of urban realism, which occupied so many Peruvian writers of the 1950's and '60's, in order to deal with different patterns of reality which also reflect the crisis of present day society.
Páginas [191]-201
Keywords: Bryce Echenique, Alfredo--Un mundo para Julius; https://purl.org/pe-repo/ocde/ford#6.02.00